A new species of Protopsyllidiidae (Hemiptera, Sternorrhyncha) from the Middle Jurassic of China - Yang, Guang; Yao, Yunzhi; Ren, Dong (Zootaxa, 2012)
A new fossil species, Poljanka hirsuta sp.n., of the family Protopsyllidiidae is described from the Middle Jurassic JiulongshanFormation of Daohugou Village, Inner Mongolia, China. A key to the species of the genus Poljanka Klimaszewski, 1995 is provided. The diagnosis of the genus is revised.